Hepatitis B virus infection in general practice across England: An analysis of the Royal College of General Practitioners Research and Surveillance Centre real-world database. Issue 5 (May 2023) - Geretti, Anna Maria; Austin, Harrison; Villa, Giovanni; Smith, Colette; Sabin, Caroline; Tsang, Ruby; Sherlock, Julian; Ferreira, Filipa; Byford, Rachel; Meza-Torres, Bernardo; Whyte, Martin; de Lusignan, Simon
Summary: Objectives: We analyzed hepatitis B surface antigen (HBsAg) screening and seropositivity within a network of 419 general practices representative of all regions of England. Methods: Information was extracted using pseudonymized registration data. Predictors of HBsAg seropositivity were explored in models that considered age, gender, ethnicity, time at the current practice, practice location and associated deprivation index, and presence of nationally endorsed screen indicators including pregnancy, men who have sex with men (MSM), history of injecting drug use (IDU), close HBV contact or imprisonment, and diagnosis of blood-borne or sexually transmitted infections. Results: Among 6, 975, 119 individuals, 192, 639 (2.8 %) had a screening record, including 3.6–38.6 % of those with a screen indicator, and 8065 (0.12 %) had a seropositive record. The odds of seropositivity were highest in London, in the most deprived neighborhoods, among minority ethnic groups, and in people with screen indicators. Seroprevalence exceeded 1 % in people from high-prevalence countries, MSM, close HBV contacts, and people with a history of IDU or a recorded diagnosis of HIV, HCV, or syphilis. Overall, 1989/8065 (24.7 %) had a recorded referral to specialist hepatitis care. Conclusions: In England, HBV infection is associated with poverty. There are unrealized opportunities to promote access to diagnosis and care for those affected.